Filamin A Is Required for NK Cell Cytotoxicity at the Expense of Cytokine Production via Synaptic Filamentous Actin Modulation - Kim, Nayoung; Yi, Eunbi; Kwon, Soon Jae; Park, Hyo Jin; Kwon, Hyung-Joon; Kim, Hun Sik (Frontiers in Immunology, 2022)
Natural killer (NK) cells are innate cytotoxic lymphocytes that efficiently eliminate malignant and virus-infected cells without prior activation via the directed and focused release of lytic granule contents for target cell lysis. This cytolytic process is tightly regulated at discrete checkpoint stages to ensure the selective killing of diseased target cells and is highly dependent on the coordinated regulation of cytoskeletal components. The actin-binding protein filamin crosslinks cortical actin filaments into orthogonal networks and links actin filament webs to cellular membranes to modulate cell migration, adhesion, and signaling. However, its role in the regulation of NK cell functions remains poorly understood. Here, we show that filamin A (FLNa), a filamin isoform with preferential expression in leukocytes, is recruited to the NK cell lytic synapse and is required for NK cell cytotoxicity through the modulation of conjugate formation with target cells, synaptic filamentous actin (F-actin) accumulation, and cytotoxic degranulation, but not granule polarization. Interestingly, we also find that the loss of FLNa augments the target cell-induced expression of IFN-γ and TNF-α by NK cells, correlating with enhanced activation signals such as Ca2+ mobilization, ERK, and NF-κB, and a delayed down-modulation of the NKG2D receptor. Thus, our results identify FLNa as a new regulator of NK cell effector functions during their decision to kill target cells through a balanced regulation of NK cell cytotoxicity vs cytokine production. Moreover, this study implicates the cross-linking/bundling of F-actin mediated by FLNa as a necessary process coordinating optimal NK effector functions.